Effect of rhPTH(1-34) and alendronate on the treatment of type 2 diabetic bone disease - Li, Huijuan; Yuan, Lingdan; Liu, Peipei; Liu, Yichen; Huang, Dongni; Ding, Huiru; Jin, Wei; Liu, Jingnan; Wang, Hongxia; Song, Lige (Frontiers in Endocrinology, 2025)
IntroductionPatients with type 2 diabetes mellitus (T2DM) have decreased bone turnover levels. However, there are few studies comparing the anti-osteoporosis effects of anabolic drugs and anti-resorptive drugs in patients with T2DM. Thus, this study was designed to compare the changes in bone mineral density (BMD) and bone turnover levels in mice and postmenopausal osteoporotic patients, both with and without T2DM, following treatment with rhPTH(1-34) or alendronate (ALN).MethodsIn the animal study, the mouse model of T2DM (DM mice) was established by high-fat diet (60% from fat) feeding and streptozotocin injection (100 mg/kg) in C57BL/6 mice. Both DM and control (CON) mice were then randomly assigned to receive either normal saline, rhPTH or ALN treatment. In the clinical study, a single-center, prospective, open-label, randomized controlled clinical trial was conducted. Postmenopausal patients with osteoporosis (OP) and postmenopausal patients with both osteoporosis and type 2 diabetes (DOP) were recruited and randomly assigned to receive either rhPTH(1-34) or ALN treatment for a period of one year. Changes in BMD and bone turnover levels were assessed in all groups.ResultsCompared to CON mice, DM mice exhibited decreased bone mass, impaired bone microstructure and, decreased levels of bone turnover markers, including procollagen type I intact N-terminal (P1NP) and C terminal cross-linking telopeptide of type I collagen (CTX). rhPTH(1-34) could reverse the low bone turnover observed in DM mice and had a better effect on improving BMD, bone volume per tissue volume (BV/TV), trabecular number in femoral trabecular bone, as well as BMD, BV/TV, and trabecular thickness in lumbar trabecular bone. In the clinical trial, at baseline, patients with DOP also exhibited decreased levels of bone turnover markers, including P1NP, CTX and osteocalcin. For patients with DOP, rhPTH(1-34) had a better effect than ALN on BMD improvement at the lumbar spine. Notably, the effect of ALN on lumbar spine improvement in patients with DOP was even smaller than that in patients with OP alone.ConclusionInitiating treatment with rhPTH(1-34) may provide greater clinical benefits to patients with diabetic bone disease characterized by low bone turnover levels.